Application of a process‐based model for predicting the productivity of Eucalyptus nitens bioenergy plantations in Spain. Issue 1 (26th March 2015) - González‐García, Marta; Almeida, Auro C.; Hevia, Andrea; Majada, Juan; Beadle, Chris
Abstract: The feasibility of using plantation‐grown biomass to fuel bioenergy plants is in part dependent on the ability to predict the capacity of surrounding forests to maintain a sustainable supply. In this study, the potential productivity of Eucalyptus nitens (Deane and Maiden) Maiden plantations grown for bioenergy in a region of north‐west Spain was quantified using the 3‐PG process‐based model. The model was calibrated using detailed measurements from five permanent sample plots and validated using data from thirty‐five additional permanent sample plots; both sets represented the variability of climate and soils of the region. Plot scale analysis showed that the model was able to reasonably estimate above‐ground biomass and water use when compared with the observed data. Using a representative loam soil characteristic, a spatial analysis was then carried out to predict the potential productivity of E. nitens for bioenergy across a potential area for plantation establishment of 2550 km 2 and to evaluate different management scenarios related to rotation length and stocking. An increase of only 1.9% in mean annual increment ( MAI ) of above‐ground biomass ( W AGB ) was found between stockings of 3000 and 5000 trees ha −1 ; for the lower stocking, MAI of W AGB increased 4% for rotation lengths between 6 and 8 years. Production was reduced by low summer rainfall and to a lesser extent by high summer and low winter temperatures, and vapour pressure deficit. Above‐ground biomass production was higher by around 12% when average rather than actual climate data were applied. The information from this study can be used to optimize forest management, determine regional relative potential productivity and contribute to decision‐making for bioenergy production from E. nitens plantations in north‐west Spain.